BCG after trimodality therapy: managing non-muscle-invasive recurrence in the irradiated bladder - Nicola Fazaa; Etan Eigner; Melissa Atallah; Yuval Shafran; Gilad Amiel; Azik Hoffman (Frontiers in Oncology, 2026)
Trimodality therapy (TMT) is an established bladder-preserving option for selected patients with muscle-invasive bladder cancer, but non-muscle-invasive recurrence remains a clinically relevant challenge. The role of intravesical bacillus Calmette–Guérin (BCG) after prior bladder-directed chemoradiation is uncertain because the available evidence is limited to small retrospective cohorts and indirect studies in previously irradiated bladders. This mini-review examines the efficacy and tolerability of BCG after TMT, the uncertain role of maintenance therapy, and the factors that should guide continued bladder preservation versus salvage cystectomy. Across available post-TMT series, BCG was feasible and durable disease control occurred in some patients; however, the small, highly selected cohorts are vulnerable to selection bias and limited statistical power, precluding definitive comparative claims or definition of an optimal induction or maintenance strategy. Careful staging is essential because radiation-related changes may complicate endoscopic assessment and pathologic interpretation. BCG may be considered when recurrence is clearly non-muscle-invasive, endoscopically manageable, and the bladder remains functional, with salvage cystectomy still feasible if treatment fails. Uncertain staging, incomplete resection, persistent or early recurrent high-risk disease, BCG-unresponsive recurrence, or poor bladder function should lower the threshold for cystectomy. Prospective studies should incorporate oncologic outcomes, treatment completion, urinary function, and cystectomy-free survival.